Charakter rodzinnych zależności i uobecnianie się wątków familiarnych w biografii i twórczości Jana Rybowicza - Litwicka, Paulina (Karkonoska Państwowa Szkoła Wyższa, 2011)
Jan Rybowicz was a poet and prose writer who lived in the years 1949-1990 in Lisia Góra near Tarnów. His writings as well as the memories preserved in letters and publications are an evidence of the poet's exceptional relations with his family. The love of the mother and the father appears to be the only stable and unconditional feeling in the tragic and lonely life of the artist. The presence of family topics in protest literature inhighly uncommon, especially in Polish literature of the 1970's and 1980's.
Keywords: Jan Rybowicz; literatura; Stare Dobre Małżeństwo; relacje rodzinne; Lisia Góra